1997
DOI: 10.1097/00006454-199710000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Late postnatal transmission of human immunodeficiency virus type 1 infection from mothers to infants in Dar es Salaam, Tanzania

Abstract: Because no HIV-1 infection occurred in children with HIV-seronegative mothers, we conclude that the observed infections at the end of the first year of life or later among children born to HIV-seropositive women were caused by late transmission from mother to child, most likely through breast-feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 19 publications
1
9
0
2
Order By: Relevance
“…Over the past few years, many studies have been conducted to improve our understanding of HIV and breastfeeding, to understand better the risk factors for HIV transmission through breastfeeding and to understand the ways to make breastfeeding safer in HIV infected women (Van de Perre et al, 1991;Ekpini et al, 1997;Karlsson et al, 1997;Kreiss 1997). In untreated women who continue breastfeeding after the first year, the absolute risk of transmission through breastfeeding is 10 -20% (Working Group, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, many studies have been conducted to improve our understanding of HIV and breastfeeding, to understand better the risk factors for HIV transmission through breastfeeding and to understand the ways to make breastfeeding safer in HIV infected women (Van de Perre et al, 1991;Ekpini et al, 1997;Karlsson et al, 1997;Kreiss 1997). In untreated women who continue breastfeeding after the first year, the absolute risk of transmission through breastfeeding is 10 -20% (Working Group, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…No case of late transmission occurred in HIV-2-infected mothers. A similar study in Dar-esSalaam with PCR and p24 antigen tests found that 8 (6%) of 139 uninfected children converted after 11 months of age [56].…”
Section: Breast-feedingmentioning
confidence: 75%
“…Late postnatal transmission (LPT), defined as HIV-1 seroconversion of infants after 4 weeks (28 days) of age, is most likely attributable to breastfeeding. 10,49,50 For reasons still unbeknownst to researchers, LPT is higher in male infants. 10 In South Africa, Coutsoudis et al have shown that exclusive breastfeeding during the first 3 months of life yielded a significantly lower risk of MTCT of HIV-1 than mixed feeding and demonstrated similar risk to no breastfeeding.…”
Section: Mechanism Of Infection Of the Breastfed Infantmentioning
confidence: 99%